Summoning compassion to address the challenges of conservation. Issue 6 (14th July 2018) - Wallach, Arian D.; Bekoff, Marc; Batavia, Chelsea; Nelson, Michael Paul; Ramp, Daniel
Abstract: Conservation practice is informed by science, but it also reflects ethical beliefs about how humanity ought to value and interact with Earth's biota. As human activities continue to drive extinctions and diminish critical life‐sustaining ecosystem processes, achieving conservation goals becomes increasingly urgent. However, the determination to react decisively can drive conservationists to handle complex challenges without due deliberation, particularly when wildlife individuals are sacrificed for the so‐called greater good of wildlife collectives (populations, species, ecosystems). With growing recognition of the widespread sentience and sapience of many nonhuman animals, standard conservation practices that categorically prioritize collectives without due consideration for the well‐being of individuals are ethically untenable. Here we highlight 3 overarching ethical orientations characterizing current and historical practices in conservation that suppress compassion: instrumentalism, collectivism, and nativism. We examine how establishing a commitment to compassion could reorient conservation in more ethically expansive directions that incorporate recognition of the intrinsic value of wildlife, the sentience of nonhuman animals, and the values of novel ecosystems, introduced species, and their members. A compassionate conservation approach allays practices that intentionally and unnecessarily harm wildlife individuals, while aligning with critical conservation goals. Although the urgency of achieving effective outcomes for solving major conservation problems may enhance the appeal of quick and harsh measures, the costs are too high. Continuing to justify moral indifference when causing the suffering of wildlife individuals, particularly those who possess sophisticated capacities for emotion, consciousness, and sociality, risks estranging conservation practice from prevailing, and appropriate, social values. As conservationists and compassionate beings, we must demonstrate concern for both the long‐term persistence of collectives and the well‐being of individuals by prioritizing strategies that do both. Abstract : Article impact statement : Protection of wildlife collectives should be guided by compassion for wildlife individuals.